A comparison of sural nerve conduction studies in patients with impaired oral glucose tolerance test - TANRIDAĞ, TÜLİN (WILEY, 2007)
Objective - Monitoring of the sural nerve is a sensitive method for detection of neuropathies. We examined different methods of studying sural nerve conduction in a group of patients with impaired glucose tolerance (IGT) in the same study. Materials and methods - Several parameters of sural nerve were investigated in 20 patients. First, sensory nerve conduction studies of the sural nerve were performed on the distal-leg and the proximal-leg segments. Second, dorsal sural nerve studies were conducted. Third, the sural/radial sensory nerve action potential (SNAP) amplitude ratios were calculated. The results were compared with those obtained from 21 healthy controls. Results - Abnormal results revealing peripheral neuropathy were found in only one patient and dorsal sural SNAP was absent in another patient (5%). Although the results of nerve conduction studies were within normal ranges except the patient with peripheral neuropathy, the lower extremity nerves and especially sural nerves have been found to be more affected and the parameters revealed large differences between groups (P < 0.05). Only dorsal sural nerve latency related to fasting blood glucose level in patients (< 0.05). Conclusions - Sural nerve studies should be of value to determine neuropathy in IGT patients. This study supported the idea that IGT is a transitional state before diabetes and also the importance of the dorsal sural nerve latencies for early detection of neuropathy.
Keywords: impaired oral glucose tolerance; electromyography; sural nerve; dorsal sural nerve; neuropathy; CLINICAL UTILITY; DIAGNOSIS; NEUROPATHY; HEALTHY